2007
DOI: 10.1002/anie.200702534
|View full text |Cite
|
Sign up to set email alerts
|

High‐Activity, Single‐Site Mesoporous Pd/Al2O3 Catalysts for Selective Aerobic Oxidation of Allylic Alcohols

Abstract: The heterogeneously catalyzed aerobic selective oxidation of hydrocarbons offers new, environmentally benign routes to a diverse range of valuable intermediates for the pharmaceutical, fine chemical, and agrochemical sectors.[1] Such powerful catalytic technologies circumvent the use of stoichiometric reagents and expensive homogeneous complexes along with the associated process disadvantages and safety issues. [2] While there has been recent interest in the potential of gold as a partial oxidation catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
248
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(258 citation statements)
references
References 32 publications
7
248
0
3
Order By: Relevance
“…Here, we note that a previous investigation also predicted a similar phenomenon on a defective oxide surface, 29 where the healing of the oxygen vacancy is believed to promote the adsorbed metal SAC clustering, and hence to reduce the selectivity and performance of the SAC. 34 On the contrary, in the present case, the remaining O atom healing the V O renders the Au atom to form a very stable bow-shaped surface O-Au-O species, with an exothermic energy of 300.069 kJ mol À1 . Therefore, the Au atom is now highly stabilized and oxidized, i.e., Q(Au) ¼ +0.64 e. Note that, recently, Wang et al 53 found that single Au cation active sites can be generated from adsorbed Au 20 clusters on TiO 2 (110), exhibiting excellent catalysis for CO oxidation.…”
mentioning
confidence: 55%
“…Here, we note that a previous investigation also predicted a similar phenomenon on a defective oxide surface, 29 where the healing of the oxygen vacancy is believed to promote the adsorbed metal SAC clustering, and hence to reduce the selectivity and performance of the SAC. 34 On the contrary, in the present case, the remaining O atom healing the V O renders the Au atom to form a very stable bow-shaped surface O-Au-O species, with an exothermic energy of 300.069 kJ mol À1 . Therefore, the Au atom is now highly stabilized and oxidized, i.e., Q(Au) ¼ +0.64 e. Note that, recently, Wang et al 53 found that single Au cation active sites can be generated from adsorbed Au 20 clusters on TiO 2 (110), exhibiting excellent catalysis for CO oxidation.…”
mentioning
confidence: 55%
“…Single-site catalysis with Pd for formic acid decomposition. As we reported above, single isolated Pd atoms supported mainly on oxide supports were shown to be active in reactions of oxidation [13][14][15] and CO 2 reduction. 16 However, for some of these reactions a deactivation of the catalyst was observed.…”
mentioning
confidence: 89%
“…Since then, the SMSI has been intensively studied on PGMs by applying various characterizations and it has been found in many other supported catalysts including Rh/TiO 2 [160], Ru/TiO 2 [161], Pd/TiO 2 [162], Pd/Al 2 O 3 [163], and so on. Taking advantage of the SMSI, it is very easy to obtain highly dispersed nanoparticles, even single atom dispersion of Pt or Pd [164][165][166].…”
Section: Strong Metal-support Interactions (Smsi) Between Metal and Tmentioning
confidence: 99%
“…Isolated Pd supported on Al 2 O 3 was reported to be efficient for the aerobic oxidation of alcohols [165]. Recently, Pt single atom supported on FeOx was reported to show excellent catalytic activity in both CO oxidation and PROX reactions [164,166].…”
Section: Figurementioning
confidence: 99%